Epileptic seizures and occupational exposure to solvents: a cases series: English - Mechergui, Najla; Youssef, Imen; Ben Charrada, Nejla; Ben Ali, Nadia; Fredj, Mohamed; Ladhari, Nizar (La Medicina del Lavoro, 2019)
Introduction: Organic solvents (OS) are substances with well-known nervous system tropism. Long-term exposure can cause several neurological and neuropsychic manifestations (mainly toxic encephalopathy). A potential causal relation between epileptic seizures and exposure to OS remains controversial. Methods: We report seven cases of patients with no neurological history who had been professionally exposed to OS and who had at least one epileptic seizure after exposure. Selection of these cases was based on medical records of patients who were referred to the occupational health department of Charles Nicolle Hospital of Tunis during the period from January 1, 2010 to December 31, 2014. Results: Cases studies concerned five men and two women aged between 29 and 46. Professional seniority ranged from 2 to 31 years. In all cases, epileptic seizures occurred after exposure to a mixture of solvents. It was concluded, according to workplace inspections, that there was an important daily and direct OS exposure. Working conditions were considered as defective. Six cases had generalized seizures, one patient presented with status epilepticus. Illness onset occurred between one and nine years after the beginning of exposure to OS. Conclusion: These cases suggest a possible relationship between OS exposure and onset of epilepsy.